Cosmocerca acanthurum n. sp. (Nematoda: Cosmocercidae) in Pseudoeurycea leprosa and Chiropterotriton orculus from the Transmexican Volcanic Belt, Central Mexico, with a checklist of the helminth parasites of plethodontid salamanders - Falcón-Ordaz, J.; Windfield-Pérez, J. C.; Mendoza-Garfias, B.; Parra-Olea, G.; de León, G. Pérez-Ponce (Zootaxa, 2007)
Plethodontid salamanders represent a group of amphibians that show a great evolutionary diversification in México, however no study of their helminth parasites had been conducted thus far. In this paper, we describe Cosmocerca acanthurum n. sp. (Nematoda: Cosmocercidae) from the intestine of the plethodontid salamanders Pseudoeurycea leprosa and Chiropterotriton orculus from Llano Grande and Texcalyacac, Estado de México, in Central México. Cosmocerca acanthurum n. sp. is easily distinguished from all other species of Cosmocerca in that females possess a uniquely spined tail, a character no seen in congeners. In addition, we compiled all the information of helminth parasites of plethodontid salamanders, and we present it in the form of a checklist of both parasite-host, and host-parasite. A brief analysis of the helminth parasite species composition is presented regarding life-history and development characteristics of plethodontids.